Production in forage sorghum intercropped with grasses and pigeon pea at crop cutting - Cruz, Sanderley; Andreotti, Marcelo; Pascoaloto, Isabô; Lima, Gilmar; Soares, Caroline (Revista Ciência Agronômica, 2020)
Due to the need to implement sustainable systems of high productivity for farming, the aim of this study was to evaluate the agronomic characteristics of forage sorghum (Sorghum bicolor (L.) Moench) intercropped with Urochloa brizantha, Megathyrsus maximum and/or pigeon pea in a non-irrigated area of a low-altitude region of the Cerrado. A randomised block design was used, of plots split over time with six treatments and four replications over two agricultural years. The treatments were (I) monocropped forage sorghum, and forage sorghum intercropped with (II) U. brizantha, (III) M. maximum, (IV) U. brizantha and pigeon pea, (V) M. maximum and pigeon pea, and (VI) pigeon pea. The following were evaluated in the sorghum and its respective intercrops: plant height, stem diameter, stand and productivity. Intercropping sorghum with M. maximum reduced fresh and dry matter production in the sorghum, albeit with no significant effect on total dry matter production for the intercrop. Sorghum intercropped with M. maximum gave a higher percentage of panicles than the other intercropped systems.